Properties of resin-treated oil palm wood heated using conventional oven and microwave with different densification parameters - Ahmad, Nurul Azwa (2015)
A study was undertaken to evaluate the physical and mechanical properties of Oil Palm Wood (OPW) treated with low molecular weight phenol formaldehyde (Lmw-PF) resin. The objectives of the study were to determine the effect of dual combination heating systems (oven heating and microwave heating) with different densification parameters on the weight gain, physical and mechanical properties of the treated OPW. A preliminary study conducted revealed that the suitable drying by combination oven with temperature 70⁰C dried until 80% moisture content (MC) and microwave heating (dried until final MC 50%) used and proceeded for the different densification parameters processes. The samples were densified to 50% densification from the thickness of 40 mm to 20 mm at a temperature of 150⁰C for three durations namely 30 minutes, 35 minutes and 40 minutes using 85 bar pressure. Four pressing cycles were applied for each process which consists of one cycle until three cycles with different compressed thickness. The compressed samples were then tested with the formaldehyde emission test, Fourier Transform Infra-Red (FTIR) as well as physical and mechanical tests. As for physical testing, the data analysis showed that the compression steps and durations did not give significant effect to the densities of the samples. The analysis also showed that the density profile between the different parts (surface and core) of the samples were also insignificant (p > 0.05). As for density gain study, the study showed that the mean percentage density gain values ranged from 94% to 116%. The compression duration and step were found to give significant effect to the density gain of the treated OPW. The weight gain study showed that the mean values range was 12.04% and 21.41% respectively. The mean water absorption values of the compressed samples were between 8.73% and 19.73%. The compression steps and durations gave significantly different to the water absorption rate of the compressed samples at P<0.05. The thickness swelling of the control samples was found to be higher than the thickness swelling of the compressed samples. Mixed results were recorded when mean values between compression durations were compared. It was hard to determine which compression duration caused a huge increment of thickness swelling since compression step may have also affected the results. The formaldehyde emission test showed that the longer compression duration and cycles gave a lower formaldehyde emission rate of the samples. However, the formaldehyde emission mean values for the treated samples were found to be too high when compared with the required FE value (0.1 mg/L) by the American National Standard Institute (ANSI) for indoor applications. Mechanical properties of the treated and untreated OPW were also assessed. Comparison on the mean values of the Modulus of Rupture (MOR) was made between each compression step and duration. The compression step and the compression duration gave no significant effect to the mean MOR values. On the other hand, the Modulus of Elasticity (MOE) results showed that the compression step gave no significant effect (p> 0.05) to the MOE of the OPW samples. Like MOR, the highest mean MOE values came from the samples impregnated with Lwm-PF compressed with compression step C:Thickness 4cm – 3.5cm – 2.5cm – 2cm (3 cycles). The compression duration did not really give significant effect in improving the elasticity of the OPW samples. The compression strength comparison showed that treated OPW performed better than untreated samples. The best mean compression strength value was 88.90N/mm²obtained from samples treated with Lwm-PF and compressed with compression step C for 40 minutes. The compression step was found to cause insignificant effect to the hardness of the OPW samples. The treated OPW samples were found superior to the control samples. The highest mean hardness value was found from the treated OPW samples compressed with compression C for 35 min.